Experimental determination of the bulk moduli of hollow nanogels. Issue 31 (28th July 2022) - Scotti, Andrea; Gasser, Urs; Petrunin, Alexander V.; Fruhner, Lisa; Richtering, Walter; Houston, Judith E.
Abstract : Small-angle neutron scattering with contrast variation is used to determine the bulk moduli of hollow nanogels. The cavity makes these nanogel extremely compressible at very low applied stress. Abstract : The softness of an object can be quantified by one of the fundamental elastic moduli. The bulk modulus of the particle is most appropriate in the presence of isotropic compressions. Here, we use small-angle neutron scattering with contrast variation to directly access the bulk modulus of polymeric nanocapsules – pNIPAM-based hollow nanogels. We show that the size of the cavity is the most important quantity that determines the softness of hollow nanogels. During initial compression, the polymer collapses into the cavity and leads to a large change in the particle volume, resulting in a very small initial bulk modulus. Once the cavity is partially occupied by the polymer, the hollow nanogels become significantly stiffer since now the highly crosslinked network has to be compressed. Furthermore, we show that the larger the cavity, the softer the nanogel.